Características clínicas - epidemiológicas y mortalidad de los neonatos prematuros del Hospital Regional de Loreto, 2019-2022 - Reátegui Rodríguez, Luis Sebastian (2024)
Objective: To determine the clinical-epidemiological characteristics and mortality of premature newborns at the Loreto Regional Hospital (HRL) from 2019 to 2022. Methodology: Observational, descriptive, correlational, cross-sectional and retrospective study. Results: 22.4% of premature newborns died; the mortality rate was 224 deaths per thousand premature newborns born alive. 52.4% of premature newborns were male; 34.3% were moderately premature (32 to <34 weeks); 61.4% had low birth weight (1500 to <2500 g.); 83.8% had appropriate weight for gestational age; 81.0% had appropriate length for gestational age; Apgar at the 1st and 5th minutes were normal (7-10 points) in 69.0% and 86.2%, respectively. 63.3% were delivered by cesarean section; 77.1% had inadequate prenatal care; 29.0% of mothers had anemia; 25.2% had preeclampsia/eclampsia; 33.3% had a UTI in the 3rd trimester; 12.9% had premature rupture of membranes. 61.0% were adult mothers (20 to <35 years) and 75.2% had secondary education. It was found that gestational age (p<0.001), birth weight (p<0.001), weight for gestational age (p=0.036), length for gestational age (p=0.003), Apgar at 1st minute (p<0.001), Apgar at 5th minute (p<0.001), maternal anemia (p=0.021), UTI in the 3rd trimester (p=0.026) and maternal age (p=0.043) had a statistically significant association with the mortality of premature newborns. Conclusions: The clinical-epidemiological characteristics and mortality of premature newborns were determined; and the association between these variables.